2006
DOI: 10.1002/pmic.200600094
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of human sperm proteins

Abstract: Conventional 1-DE has in the past provided a wealth of information concerning the major sperm proteins. However, so far there are relatively few reports exploiting the potential of the present proteomic tools to identify and to study additional yet-unidentified important proteins present in human spermatozoa. In the present work, 2-DE of proteins extracted from human normozoospermic spermatozoa led to the resolution of over 1000 spots. Subsequent excision from the gels of 145 spots and MALDI-TOF MS analysis al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(192 citation statements)
references
References 49 publications
11
177
1
1
Order By: Relevance
“…Reverse transcription-polymerase chain reactions (RT-PCR) for the synthesis of complementary DNA (cDNA), 12 μL aliquots of master mixture containing 100 ng of human testes RNA, 1 μL of 500 ng/μL oligo(dT) [12][13][14][15][16][17][18] primer (Invetrogen, Grand Island, NY, USA), and 9 μL of diethylpyrocarbonate-treated water were heated to 70°C for 10 min and put on ice. RT reactions were performed in 20 μL containing master mixture, 4 μL of 5X first-strand synthesis buffer, 0.1 M dithiothreitol, 10 mM of each dNTP, and 200 units of Superscript TM II RNase H -reverse transcriptase (Invetrogen, Grand Island, NY, USA).…”
Section: Reverse Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reverse transcription-polymerase chain reactions (RT-PCR) for the synthesis of complementary DNA (cDNA), 12 μL aliquots of master mixture containing 100 ng of human testes RNA, 1 μL of 500 ng/μL oligo(dT) [12][13][14][15][16][17][18] primer (Invetrogen, Grand Island, NY, USA), and 9 μL of diethylpyrocarbonate-treated water were heated to 70°C for 10 min and put on ice. RT reactions were performed in 20 μL containing master mixture, 4 μL of 5X first-strand synthesis buffer, 0.1 M dithiothreitol, 10 mM of each dNTP, and 200 units of Superscript TM II RNase H -reverse transcriptase (Invetrogen, Grand Island, NY, USA).…”
Section: Reverse Transcriptionmentioning
confidence: 99%
“…HIBADH is expressed in rat liver, heart, muscle, kidney, and cultural neural cells [34,41]. A larger-scale proteomic study identified approximately 100 proteins in mature human sperm, including HIBADH [18]. However, its detailed expressional patterns in different human organs and developmental stages have not Fig.…”
Section: Expression Patterns Of Hibadh In Mature Human Spermatozoamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, Johnston et al 42 used an LC-MS approach to identify 1760 proteins in human sperm. Then in 2006, Martínez-Heredia et al 43 provided a reference two-dimensional map of the mature human sperm proteome with 131 proteins identified. Other studies have also revealed a similar number of proteins.…”
Section: Functional Proteomics Of a Human Model Of Abnormal Spermatogmentioning
confidence: 99%
“…ATP synthase also had hits with high scores, which is consistent with the importance of energy production in sperm. Martinez-Heredia et al (2006) identified 98 proteins in human sperm using 2D-gel and matrix-assisted laser desorption-ionization time-of-flight mass spectrometry. We identified 74 proteins in the sea star sperm tail.…”
Section: Discussionmentioning
confidence: 99%